Analysis of Workplace Health Education Performed by Occupational Health Managers in Korea - Yeon-Ha Kim, RN, PhD; Moon-Hee Jung, RN, PhD (Elsevier, 2016)
Purpose: To evaluate workplace health education as practiced by occupational health managers based on standardized job tasks and suggest priority tasks and areas to be trained. Methods: The study was conducted between November 10, 2013 and April 30, 2014. The tool used in this study was standardized job tasks of workplace health education for occupational health managers which was developed through methodological steps. It was evaluated by 233 worksite occupational health managers. Data were analyzed using SPSS 21.0. Results: Predicting variables of workplace health education performance were the "analysis and planning" factor, type of enterprise, and form of management. Healthcare professionals and occupational health managers who managed the nonmanufacturing industry showed high importance and low performance level in "analysis and planning" factor. Conclusions: "Analysis and planning" skill is priority training area for healthcare professionals and occupational health managers who managed nonmanufacturing industry. It is necessary to develop a training curriculum for occupational health managers that include improving analysis of worksites and plans for a health education program.